Forensic genealogy: Some serious concerns. (September 2018) - Syndercombe Court, Denise
Abstract: Genealogical databases have provided links to possible perpetrators of crimes in several cold cases in the US. This commentary discusses some of the ethical issues associated with this approach while recognising the underlying value of the identifications.